Analysis of junior high school students' critical mathematical thinking ability in solving similarity problems - Evin Susanti; Syarifah Fadillah; Jamilah Jamilah (Universitas Sarjanawiyata Tamansiswa, 2025)
This research seeks to elucidate students' critical thinking abilities about comparable content. This study is descriptive in nature and employs a qualitative methodology. This study employs a case study methodology. The obtained data comprises critical thinking ability exam results, which include two problems and interviews. The obtained data is assessed according to the critical thinking skill indicators established by the researcher, which include: 1) investigating; 2) recognizing and justifying ideas; 3) generalizing; 4) clarifying and resolving. This research employs data analysis methodologies from Miles and Huberman, including data collection, data reduction, data presentation, and conclusion drawing/verification. The triangulation approach ensures the authenticity of the data used in this investigation. The data analysis findings categorize students' cognitive capacities into three groups: 11.11% (4 students) are classified as high, 27.78% (10 students) as medium, and 61.11% (22 students) as low. From the perspective of critical thinking capacity, 100% of students explored the topic, 55.56% identified and justified the notion, 16.67% generalized, and 11.11% clarified and resolved the issue. These findings demonstrate that students’ overall critical thinking abilities in solving similarity problems are still low, particularly in generalizing and resolving problems. The study contributes theoretically by reinforcing the significance of critical thinking in mathematics education, particularly geometry; methodologically by integrating test and interview data to analyze thinking processes; and practically by offering insights for teachers to develop instructional strategies that foster students' ability to think critically and solve problems effectively.